Simplified seismic design approach for steel portal frame piers with hysteretic dampers. - Chen, Zhiyi
A simplified seismic design procedure for steel portal frame piers installed with hysteretic dampers is proposed, which falls into the scope of performance-based design philosophy. The fundamental goal of this approach is to design a suite of hysteretic damping devices for existing and new bridge piers, which will assure a pre-defined target performance against future severe earthquakes. The proposed procedure is applicable to multi-degree-of-freedom systems, utilizing an equivalent single-degree-of-freedom methodology with nonlinear response spectra (referred to as strength-demanded spectra) and a set of formulae of close-form expressions for the distribution of strength and stiffness produced in the structure by the designed hysteretic damping devices. As an illustrative example, the proposed procedure is applied to a design of a simple steel bridge pier of portal frame type with buckling-restrained braces (one of several types of hysteretic dampers). For the steel portal frame piers, an attempt is made to utilize not only the displacement-based index but also the strain-based index as pre-determined target performance at the beginning of design. To validate this procedure, dynamic inelastic time-history analyses are performed using the general-purpose finite element program ABAQUS. The results confirm that the proposed simplified design procedure attains the expected performance level as specified by both displacement-based and strain-based indices with sufficient accuracy.
Keywords: Simplified seismic design; Performance-based design; Steel bridge; Hysteretic damper; Time-history analysis